Randomized Controlled Clinical Trial to Access Efficacy and Safety of Miltefosine in the Treatment of Cutaneous Leishmaniasis Caused by Leishmania (Viannia) guyanensis in Manaus, Brazil - Chrusciak-Talhari, Anette (The American Society of Tropical Medicine and Hygiene, 2011)
Miltefosine has been used in the treatment of several new world cutaneous leishmaniasis (CL) species with variable efficacy. Our study is the first evidence on its clinical efficacy in Leishmania (Viannia) guyanensis. In this phase II/III randomized clinical trial, 90 CL patients were randomly allocated (2:1) to oral miltefosine (2.5 mg/kg/day/28 days) (N = 60) or parenteral antimony (15–20 mg/Sb/kg/day/20 days) (N = 30) according to age groups: 2–12 y/o and 13–65 y/o. Patients were human immunodeficiency virus (HIV) noninfected parasitological proven CL without previous treatment. Definitive cure was accessed at 6 months follow-up visit. No severe adverse events occurred. Vomiting was the most frequent adverse event (48.3%) followed by nausea (8.6%) and diarrhea (6.7%). Cure rates were 71.4% (95% confidence interval [CI] = 57.8–82.7) and 53.6% (95% CI = 33.9–72.5) (P = 0.05) for miltefosine and antimonial, respectively. There were no differences in cure rates between age groups within the same treatment arms. Miltefosine was safe and relatively well tolerated and cure rate was higher than antimony.